Second opinion and time to knee arthroplasty: a prospective cohort study of 142 patients - Kisch, Rebecca; Grill, Eva; Müller, Martin; Pietzner, Jens; Paulus, Alexander C.; Weigl, Martin (BMJ open, 2023)
Objective The objective of this study was to determine the impact of obtaining a second opinion consultation on time to knee arthroplasty (KA). We further examined the frequency of KA and the determinants of KA following the second opinion. - Design Prospective cohort study. - Setting The second opinion programme was implemented at the Ludwig Maximilian University Hospital in Munich. - Participants Participants comprised patients with knee osteoarthritis who were insured with one of the largest statutory health insurance Allgemeine Ortskrankenkasse Bayern (mean age 64.3±9.6 years). Patients participated in a second-opinion programme and completed questionnaires on site before and after personal presentation for the second opinion consultation. Follow-up questionnaires were delivered by post at 3 and 12 months after the second opinion consultation. Of the 142 patients included in the study, 47 (33.1%) underwent KA within 12 months after obtaining the second opinion. - Primary outcome measures Primary outcome measure was time until patients received KA. Cox proportional hazard modelling was used to calculate the associations between the selected predictors and time that elapsed between receipt of the second opinion to KA. - Results Mean time until KA was 17 weeks. Kaplan-Meier curves showed significant differences in time to KA according to the recommendation given at second opinion consultation, knee-related quality of life and Kellgren-Lawrence grade. In multivariate Cox proportional hazard modelling, second opinion recommendation (HR 5.33, 95% CI 1.16, 24.41) and knee-related quality of life (HR 1.03, 95% CI 1.01, 1.06) were significant predictors of time from second opinion to KA. - Conclusions Obtaining a second opinion had significant impact on time to knee replacement. Those who were recommended immediate surgery also underwent surgery more quickly after the second opinion. The effect of knee-related quality of life supports the importance of patient-reported outcome measures in the decision for or against KA.
Gesehen am 01.12.2023